Optimalisasi Layanan Aktivasi IKD dalam Mendukung Transformasi Digital Administrasi Kependudukan di Kelurahan Kalisari Kota Surabaya - Maulidya, Dinta Fernanda; Widiyarta, Agus (VISA: Journal of Vision and Ideas, 2024)
The development of information technology has made the government continuously innovate by implementing the concept of digitalizing public services, including in the scope of population administration. Surabaya, with a population of 2,893,698 people, certainly faces various dynamics of population administration issues that demand the government to effectively and efficiently address these problems through the e-Government system. One of them is by launching the Digital Population Identity application that includes the ID card and family card with a centralized system under the Ministry of Home Affairs, starting from 2023. The aim of this research is to determine the optimization efforts of the IKD activation service in supporting the digital transformation of population administration in the Kalisari sub-district of Surabaya. In this research, the author uses a qualitative method with a descriptive approach model and utilizes primary data obtained from observations, interviews, and direct documentation at the research site. Meanwhile, secondary data is obtained through literature studies by tracing references such as books, scientific articles, data graphics, and previous research. The research results with optimization theory show that the efforts to optimize the IKD activation service in Kalisari sub-district can be categorized as good, but have not yet reached maximum evenness due to the presence of residents who are not aware of the urgency of population administration order. Therefore, there is a need for a new, more intensive strategy to increase the percentage of IKD ownership in the Kalisari sub-district of Surabaya.